Criminal Redistribution of Stolen Property: The Need for Law Reform - Blakey, G. Robert (1976)
Section I of this article describes various theft and fencing operations. As will be evident from that discussion, the most sophisticated fences are far removed from those receivers who are owners of seedy pawnshops or who indiscriminately select potential customers on the street, and thus they pose peculiar problems for law enforcement. Section II then identifies inadequacies in existing investigative techniques and in the substantive laws of receiving in light of modern theft and fencing operations. It proposes changes in the law and suggests appropriate law enforcement strategies to facilitate the detection and conviction of alleged fences. Needed changes in the civil law are also discussed. Throughout these sections of the article, reference will be made to the provisions of a Model Theft and Fencing Act set forth in appendix B